Large Trades on the Tunisian Stock Exchange: Downstairs versus Upstairs Stock Markets (Global Journal of Management and Business Research, 2012)
This study examines the price impact differences between large trades routed to the central market and blocks traded on the upstairs market, on the Tunisian Stock Exchange. The results show that large transactions affect stock prices, whether they are routed upstairs or downstairs. In addition, these price impacts are quite different depending on where the execution takes place, especially around large sales. The results of empirical investigations also show that, when an upstairs market is governed by too restrictive rules and when brokers don#x2019;t have the reflex or avoid trading upstairs, block market does not necessarily improve cost execution.
Keywords: upstairs market; fragmentation; cost execution; price impact; and trade difficulty